Shortcomings and prospects of Ukrainian sausage producers on the world market - Tatsiyenko, Nataliya; Berezovska, Olga (My University, 2015)
The place of Ukrainian sausage producers and their prospects on the world market are revealed. It has been determined the top of the largest producers and their current problems are analyzed. Розглядається місце українських виробників ковбас та їх перспективи на світовому ринку. Визначено найкрупніших виробників, аналізуються проблеми, які вони мають на даний момент.
Keywords: sausages; quality; ковбаси; якість; колбасы; качество; кафедра ділової іноземної мови та міжнародної комунікації